Concepts in thermal physics - Blundell, Stephen, 1967-; Blundell, Katherine M. (Oxford : Oxford University Press, 2010)
This text provides a modern introduction to the main principles of thermal physics, thermodynamics and statistical mechanics. The key concepts are presented and new ideas are illustrated with worked examples as well as description of the historical background to their discovery.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Thermodynamics; Heat